The power of translanguaging by Papuan non-EFL students during EFL virtual class - Sahib, Rahmawansyah; Yamin, Ade; Sileuw, Marwan; Zulihi, Zulihi (Universitas Islam Negeri Banda Aceh, 2024)
The study focuses on addressing a knowledge gap in learning English for non-EFL students in higher education in Papua. Non-EFL students in Papua sometimes find English unattractive, if not frightening. Translanguaging helps non-EFL students to acquire and practice English skills in virtual classrooms. The purpose of this study is to investigate the process of non-EFL students' virtual EFL learning through translanguaging. A qualitative study was conducted through interviews and observations with EFL teachers and non-EFL students attending English classes. There are several non-English departments in one of the higher education institutions in Papua, which are sources of information in this study. The data are then analyzed qualitatively using a discourse analysis framework. The results of the study show that the power of translanguaging for non-EFL students is an option that is always used during virtual English learning. The process of virtual English learning uses different digital learning platforms such as Zoom meetings, WhatsApp groups and Google classroom. The use of this platform has its own privileges as long as it is used in virtual English learning with translanguaging. The process of learning English using different platforms can be described by two activities, such as teacher activities using translanguaging and student activities. Virtual English learning using translanguaging is also illustrated by the use of various language resources owned by students. This is an added value of virtual EFL learning using translanguaging. Therefore, it is highly recommended that EFL teachers use translanguaging during the virtual EFL teaching process to make it easier for non-EFL students to understand EFL subjects.